Pembatalan Perjanjian Perikatan Jual Beli Hak Atas Tanah Secara Sepihak - Baiq Silfiana (Jatiswara, 2016)
This research aims to analyze the annulment of agreements binding sale and purchase rights over land unilaterally. Particularly related to the validity of the agreement and selling land rights by using a binding sale and purchase deed and its cancellation. Based on the results showed: (1) the treaty binding sale and purchase agreements is born of nature opens in Book III of the book of law civil law (KUHPer). Binding agreement and selling these arise due to things (requirement) that have not been fulfilled or things (requirements) was agreed upon by the parties must be met, for example, are related to the payment of the price has not been paid. (2) changes to the price that has been disepakti by the parties previously could only be done if there is agreement from both parties in this case the seller and the buyer. This means that adjustment against price in selling land rights cannot be used as an excuse by the seller to cancel the agreement unilaterally.